Essentials of physical geography - Gabler, Robert E. (Thomson Brooks/cole, 2007)
Essentials of physical geography emphasizes three essential themes to demonstrate the major roles for the discipline--Geography as Physical Science, Geography as Spatial Science, and Geography as Environmental Science. With a renewed focus on examining relationships and processes among systems, the text helps you understand how the various systems interrelate.